Schizophyllum commune maxillary sinusitis in an immunocompromised patient: A case report (Indian Journal of Case Reports, 2022)
Schizophillum commune is a basidiomycotic fungus which grows ubiquitously on trees and rotting wood. Human infections caused by it are although of diverse presentation but are very rare. We present a case of sinusitis caused by Schizophyllum commune in a 58-years-old female patient post COVID 19 infection with a history of allergic rhinitis and diabetes mellitus type 2. CT scan findings established the clinical diagnosis of fungal maxillary sinusitis which was confirmed with culture report and PCR followed by sequencing. Patient underwent functional endoscopic sinus surgery. She was treated empirically with Itraconazole after surgical excision.